A case of a suicide attempt with sitalopram causing supression of sinusal rhythm with development of atrial rhythm - Korkmaz, Sevda; Korkmaz, Hasan; Atmaca, Murad; Kuloglu, Murat (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2011)
Selective serotonine reuptake inhibitors (SSRI) are known as effective and quite safe antidepressant drugs which inhibit seratonin reuptake in the presynaptic area without affecting the noradrenaline and dopamine reuptake. Nevertheless, in high dose use of all antidepressants, including SSRI, some toxic effects might be observed in central nervous system, respiratory system and cardiovascular system. In our article, we present a case who developed electrocardiographic changes due to use of citalopram in high doses.
Sitalopram ile suisid girişimi sonrasinda sinüs ritminin baskilanarak atrial ritmin gelişti?i bir olgu
Keywords: Suicide; citalopram; atrial rhythm